Evaluation of immersive virtual reality locomotion mechanisms - Tanaka, Eduardo; Paula, Tiago; Silva, Alisson; Antunes, Victor; Domingues, Leonardo; Almeida, Lucimara; Alves, Alex; Oliveira, Roberta (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2020: Anais do XIX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2020)
Motion sickness is one of the most common issues that affects the user experience in immersive virtual reality environments. In general, a user feels motion sickness because the brain perceives a movement but his/her body is not actually moving. In immersive virtual reality, this is caused because, frequently, the user’s field of view is blocked by a head-mounted display and the locomotion in the virtual world is performed by moving analog sticks in a gamepad-like device (this is also known as artificial locomotion). In addition to some general best practices and guidelines to prevent motion sickness and provide immersion, several different locomotion mechanisms have been conceived in the last few years, both in the academy and in the industry. This paper presents the findings from usability tests to compare different locomotion mechanisms. The evaluation took into account not only the level of motion sickness observed in the participants, but also the ease of learn and use, the subjective preferences and the sense of immersion. It is expected that the data from these tests will assist the development of immersive virtual reality environments and future enhancements of locomotion mechanisms for immersive virtual reality.